2014
DOI: 10.1371/journal.pone.0111087
|View full text |Cite
|
Sign up to set email alerts
|

An Obligatory Role of NF-κB in Mediating Bone Marrow Derived Endothelial Progenitor Cell Recruitment and Proliferation Following Endotoxemic Multiple Organ Injury in Mice

Abstract: BackgroundRecruitment of bone marrow derived endothelial progenitor cells (BMDEPCs) alleviates multiple organ injury (MOI) and improves outcomes. However, mechanisms mediating BMDEPC recruitment following septic MOI remain largely unknown. This study characterized the kinetics of BMDEPC recruitment and proliferation and defined the role of NF-κB in regulating BMDEPC recruitment and proliferation.Methods and Main FindingsChimeric mice with an intact or disrupted NF-κB p50 gene and BMDEPC-restricted expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…CHIKV infects endothelial cells in vivo (37, 169) and edema is a well-known symptom of CHIKV infection (47, 82). Endothelial barrier repair requires NF-κB activation (170, 171) and a NF-κB to AP-1 transition (172). Herein we provide evidence that butyrate promoted certain AP-1 activities and markedly inhibited canonical NF-κB pathways, consistent with previous studies on butyrate (3134, 142).…”
Section: Discussionmentioning
confidence: 99%
“…CHIKV infects endothelial cells in vivo (37, 169) and edema is a well-known symptom of CHIKV infection (47, 82). Endothelial barrier repair requires NF-κB activation (170, 171) and a NF-κB to AP-1 transition (172). Herein we provide evidence that butyrate promoted certain AP-1 activities and markedly inhibited canonical NF-κB pathways, consistent with previous studies on butyrate (3134, 142).…”
Section: Discussionmentioning
confidence: 99%
“…Systemic mobilization of EPCs into the peripheral blood increases in the setting of either local or systemic organ dysfunction, prompting interest in their use as a potential biomarker for various disease processes [ 107 ]. Additionally, increased EPC recruitment to various organs, including the lung, liver, and kidney has shown physiologic benefit [ 112 ]. However, despite these correlations, their actual contribution to organ repair remains an area of contention.…”
Section: Trauma Pathophysiologymentioning
confidence: 99%
“…Their role in vasculogenesis-previously thought to occur only via migration of existing endothelial cells or through induction of hematopoietic stem cells-has been wellestablished [107]. Several studies have shown a correlation between the presence of EPCs in blood to various disease processes, including neurologic and cardiovascular disease, sepsis, malignancy, and severe trauma, among others [108][109][110][111][112]. Given their ubiquitous nature and the importance of endothelial maintenance and neovascularization to wound healing, EPCs are an encouraging option for future trauma therapies.…”
Section: Endothelial Progenitor Cellsmentioning
confidence: 99%
“…Interestingly, there are data, both in mice and humans, indicating that LPS/endotoxemia can mobilize bone marrow-derived EPCs to assist lung repair after bacterial pneumonia [98]. NF-κB has been shown to play a fundamental, yet organ-specific role in the mobilization, recruitment and proliferation process [99].…”
Section: Other Adult Stem and Progenitor Cellsmentioning
confidence: 99%